THE IMPACT OF LIBERALIZATION ON THE DEVELOPMENT OF THE SOCIAL SYSTEM - Khujamov Khayitboy; Rizaev Ilhom (International Engineering Journal For Research & Development, 2020)
The study of society as a system is one of the most pressing problems of modern science. Synergetic studies show that the potential for self-organization in complex, holistic, heterogeneous, organic, dissipative, open, non-linear systems is high. Previously, scientists focused on the study of stable, dynamic laws of existence, but now the paradigm is focused on the study of unstable states and static laws of existence, and this has become an urgent problem. The research of self-organizing factors of society has brought new results. In particular, it was found that instability, chaos, entropy, fluctuations and bifurcations are normal conditions when social systems move away from equilibrium. The destructive and constitutive nature of these situations has been studied. In particular, it was noted that chaos would destroy the old system and facilitate the self-organization of the new system.